Dissection of hepatic versus extra‐hepatic insulin clearance: Ethnic differences in childhood. Issue 12 (20th August 2018) - Piccinini, Francesca; Polidori, David C.; Gower, Barbara A.; Fernandez, Jose R.; Bergman, Richard N.
Abstract : Aims: Adult African American (AA) women have one third of the hepatic insulin clearance of European American (EA) women. This lower hepatic (but not extra‐hepatic) insulin clearance in AA individuals is associated with higher plasma insulin concentrations. This study aims to understand whether impairment of hepatic insulin clearance is seen in AA individuals since childhood, possibly suggesting that genetic/epigenetic factors, rather than lifestyle only, contribute to this. Materials and methods: A total of 203 children (105 male and 98 female (55 AA, 88 EA and 60 Hispanic American [HA]; ages, 7‐13 years; mean BMI, 19 kg/m 2 )) underwent the frequently applied intravenous glucose tolerance test (FSIGT) at the University of Alabama at Birmingham, General Clinical Research Center and Department of Nutrition Sciences. Glucose, insulin and C‐peptide levels were measured and hepatic and extra‐hepatic insulin clearances were calculated using mathematical modelling. Results: Fractional hepatic insulin extraction (FEL ) was lower in AA than in EA children (mean (SD), 19% (20%) vs 33% (20%); P = 0.0007). Adjusting for age, Tanner stage and body fat, FEL was lower in AA than in EA children ( P = 0.0012), and there was a slight sex‐related difference (FEL, 24% (10%) vs 29% (10%) in boys vs girls; P = 0.04). Extra‐hepatic insulin clearance did not differ with ethnicity (27 (12), 21 (12) and 24 (28) mL/kg/min for AA, HA and EA children, respectively; P > 0.05). Conclusions: At a young age, FEL is lower in AAs than in EAs, which does not rule out genetic/epigenetic factors. These differences are related to hyperinsulinaemia and, over time, could possibly contribute to metabolic disorders in AA individuals.